The mediating role of body mass index in the association between unprocessed or minimally processed foods and gallstones - Jiang, Chenyu; Zhu, Luqi; Teng, Xiaosheng; Wen, Hongxun; Yu, Zhenjun; Yang, Weiwei; Shao, Yaojian (Frontiers in Nutrition, 2025)
BackgroundThe extent of food processing significantly impacts human health, with ultra-processed foods (UPFs) linked to numerous adverse health outcomes. In contrast, research on unprocessed or minimally processed foods (MPFs) and their association with gallstones remains scarce. This study aimed to investigate the relationship between MPF intake and gallstones in U.S. adults.MethodsWe conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES, 2017–2023). MPF intake was assessed according to the NOVA classification system. Survey-weighted logistic regression, restricted cubic spline models, and mediation analyses were employed to evaluate the association between MPF consumption and gallstones disease.ResultsAmong 11,779 U.S. adults, 1,303 cases of gallstones disease were identified (weighted prevalence: 9.8%). Elevated percentage contribution of MPF was significantly associated with a reduced likelihood of gallstones [model 1, odds ratio (OR): 0.40, 95% confidence interval (CI): 0.21–0.78], and this inverse relationship persisted after full adjustment (model 3; OR: 0.28, 95% CI: 0.09–0.84). Compared to the lowest quartile (Q1), the highest quartile (Q4) of MPF consumption showed significantly lower odds of gallstones (OR: 0.72, 95% CI: 0.53–0.98). A non-linear, inverted U-shaped relationship was observed between MPF intake and gallstones (overall p < 0.001; non-linear p = 0.031). Mediation analysis indicated that the body mass index (BMI) partially mediated this association. No significant associations were found between other NOVA food groups, including UPF, and gallstones disease.ConclusionHigher MPF consumption is associated with a lower risk of gallstones disease, with BMI partially mediating this relationship.